Los procedimientos de emergencia en la contratación pública (Tema Central) - Díaz Colmachi, Juan Francisco (2018)
On Saturday, April 16, 2016, around 19h00, the earthquake started in front of the Ecuador coasts. The next day was different for Esmeraldas, Manabí and the whole country. Talking about public procurement, takes too long to rebuild the devastated areas. A year later, was analyzed how to proceeded in the emergency; the actions of the public administration and its officials in a state of emergency and verify the integral reparation.